To solve the equation \( 4.5 - 7 = 2(y + 2.25) + 6.6 \), we will go step by step and apply a different property at each step.
Step 1: Simplify the left side.
Calculate \( 4.5 - 7 \):
\[
4.5 - 7 = -2.5
\]
Now, we rewrite the equation:
\[
-2.5 = 2(y + 2.25) + 6.6
\]
Property used: Subtraction Property of Equality (we simplified one side of the equation).
Step 2: Move the constant on the right side.
Subtract \( 6.6 \) from both sides:
\[
-2.5 - 6.6 = 2(y + 2.25)
\]
Calculating the left side:
\[
-2.5 - 6.6 = -9.1
\]
Now the equation is:
\[
-9.1 = 2(y + 2.25)
\]
Property used: Addition Property of Equality (we moved the constant to the other side).
Step 3: Divide both sides by 2.
\[
\frac{-9.1}{2} = y + 2.25
\]
Calculating the left side:
\[
\frac{-9.1}{2} = -4.55
\]
The updated equation is:
\[
-4.55 = y + 2.25
\]
Property used: Multiplicative Property of Equality (we divided both sides by 2).
Step 4: Subtract \( 2.25 \) from both sides.
\[
-4.55 - 2.25 = y
\]
Calculating the left side:
\[
-4.55 - 2.25 = -6.8
\]
So we have:
\[
y = -6.8
\]
Property used: Subtraction Property of Equality (we moved the constant \( 2.25 \) to the other side).
Final Answer:
The value of \( y \) is \( -6.8 \).
Properties Used in Order:
- Subtraction Property of Equality
- Addition Property of Equality
- Multiplicative Property of Equality
- Subtraction Property of Equality